An appropriate and reactive response to the repeated waves of the COVID-19 pandemic by the national medico-psychological network (CUMP) in France. (May 2022) - Prieto, Nathalie; Vignaud, Philippe; Darbon, Remy; Cheucle, Eric; Philippe, Jean-Marc
Introduction: France has been impacted by the COVID-19 pandemic. Anxiety, depression, burn out and the high proportion of post-traumatic stress disorder proved to be the most expected troubles caused by this pandemic and the confinement. Medico-psychological emergency units (CUMP) have been solicited at the very early stage of the pandemic because CUMP units are very well known by the French government and systematically associated to emergency plans. Methods: In this article we describe the process which has been developed to cope with the psychological needs in the general population. At a first level, platforms of volunteers specialised into listening were available. Then those platforms could directly mobilise the CUMP in case of psychiatric disorders. It ran over the whole first wave and it has been reactivated because of the second confinement in France. Results: During the first wave, approximately 1% of all the calls made on the national Covid number required to be redirected to the listening platforms. Of this group, 4% were related to reactive pathology or a psychiatric decompensating that required adapted and specialised care. Conclusion: The high rates of psychological distress detected in the general population in recent scientific literature seem discrepant with our findings of relatively low reorientation towards the CUMP. Nevertheless, our study highlights that the response of the CUMP network in France during the first wave was supportive. The second wave displays its adaptability to the public health policies.